PERAN INFLUENCER, FITUR LIVE STREAMING, DAN ELECTRONIC WORD OF MOUTH TERHADAP KEPUTUSAN PEMBELIAN PRODUK KOSMETIK PADA APLIKASI TIKTOK SHOP (Studi Kasus Wanita Karir Di Kecamatan Pulau Punjung) - Endah Juliati Endah; Fenisi Resty; Dini Elida Putri (MANAJEMEN DEWANTARA, 2025)
TikTok has been widely known in Indonesia since 2018, especially among young people. However, since the Covid-19 pandemic in 2020, TikTok's popularity has skyrocketed. Many people use TikTok to fill their free time, seek entertainment, and various activities. Until 2024 TikTok has become one of the most widely used social media applications in Indonesia with millions of daily active users. This study aims to identify the role of influencers, live streaming features, and electronic word of mouth that influence purchasing decisions for cosmetic products at TikTok Shop. This study uses a quantitative research method with data collection using a questionnaire conducted from February to April with a population of 2,176 respondents and a sample of 338 respondents calculated using the Slovin formula. The results of this study indicate that the variables of Influencer Role, Live Streaming Features, and Electronic Word Of Mouth partially and simultaneously have a positive and significant effect on Purchasing Decisions of Career Women in Pulau Punjung District, Dharmasraya Regency. The R2 value is 0.568, which means that all independent variables can influence the dependent variable by 56.8% while the remaining 43.2% is influenced by other factors not tested in this study.